Factors affecting direct lightning strike damage to fiber reinforced composites: A review. (15th February 2020) - Kumar, Vipin; Yokozeki, Tomohiro; Karch, Christian; Hassen, Ahmed A.; Hershey, Christopher J.; Kim, Seokpum; Lindahl, John M.; Barnes, Abigail; Bandari, Yashwanth K.; Kunc, Vlastimil
Abstract: In recent years, Carbon Fiber Reinforced Plastics (CFRP) or Glass Fiber Reinforced Plastics (GFRPs) have become a very common material for aircraft and wind turbine structures. These structures are often protected from lightning strikes using conventional metal-based protective films/foils. Non-conventional, non-metallic lightning strike protection (LSP) technologies have not yet been fully realized, but research on non-conventional LSP systems for CFRPs has gained momentum in the last few years. The discovery of new structural conductive materials and improvements in the processing of carbon nano-filler based composites have challenged the conventional metal-based LSP systems by providing the potential for lightweight, non-metallic alternatives. However, a major challenge in using non-conventional LSP is the complex nature of a lightning strike event and its complicated thermal and mechanical impact on CFRP structures. Understanding the direct effect of a lightning strike on a CFRP structure requires understanding multiple transient loads, such as electrical, thermal, magnetic, acoustics, shock, and inertia. This review article focuses on new findings and discusses the complex direct effects of lightning on CFRPs. The focus is to find the important factors that regulate and control the damage to FRPs and they are classified and discussed with the help of available literature based on experimental results. Possibilities and limitations to these new findings are also discussed.